2018
DOI: 10.3389/fmicb.2018.00797
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity and Nitrogen Utilization Strategies in the Upper Layer of the Northwestern Pacific Ocean

Abstract: Nitrogen (N) is a primary limiting nutrient for bacterial growth and productivity in the ocean. To better understand bacterial community and their N utilization strategy in different N regimes of the ocean, we examined bacterial diversity, diazotrophic diversity, and N utilization gene expressions in the northwestern Pacific Ocean (NWPO) using a combination of high-throughput sequencing and real-time qPCR methods. 521 and 204 different operational taxonomic units (OTUs) were identified in the 16s rRNA and nifH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 68 publications
(74 reference statements)
5
22
0
Order By: Relevance
“…In addition, the similar turnover time of NH 4 + and urea (2.6 ± 2.0 vs. 2.8 ± 1.4 d) with respect to uptake may also point to the importance of urea, as previous studies (e.g., McCarthy ; Harrison et al ; Berman and Bronk ; Solomon et al ). The abundant urea transporters detected by proteomic analysis in the same cruise (Li et al ) was also supportive of the importance of urea.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the similar turnover time of NH 4 + and urea (2.6 ± 2.0 vs. 2.8 ± 1.4 d) with respect to uptake may also point to the importance of urea, as previous studies (e.g., McCarthy ; Harrison et al ; Berman and Bronk ; Solomon et al ). The abundant urea transporters detected by proteomic analysis in the same cruise (Li et al ) was also supportive of the importance of urea.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, the amount of the bacterial OTUs was not necessarily correlated with location. The amounts of the bacterial OTUs in samples greatly varied depending on several physicochemical and environmental factors [29,30]. Other studies revealed that the seawater collected from Gosung Bay (the South Sea of Korea) and Mallorca Island in Spain had only 900 OTUs [7] and 965 OTUs [12], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Primers were designed using the online Primer3 Input (v0.4.0) (Supplementary Table S1 ). PCR products of cDNA were separated on agarose gels and sequenced to ensure the specificity and accuracy as described by Li et al (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Amplification curves and melt curves were monitored to test the integrity and stringency of the reactions. Relative gene expression was calculated as described by Li et al (2018) and normalized using the internal control gene (actin transcript) ( McGinn and Morel, 2008 ).…”
Section: Methodsmentioning
confidence: 99%